(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2020)
Calamine or rust scale is an important residue of steelmakers, mainly steel mills; This waste represents an environmental and economic problem for the different companies, taking into account that this material can be used by reincorporating it in a productive process. The purpose of this paper is to investigate and evaluate the structural incidence of partial substitution of the fine aggregate of a granular base (BG- 38) with calamine. Two tests were carried out with granular base material supplied by the Solarte-Solarte consortium; a control test with three specimens (without calamine) manufactured with a different level of compaction as stipulated in the standard for conducting the CBR test (5 layers of compaction with 10, 25 and 56 strokes); and the second with three specimens replacing 35.53% of the fine material with calamine; also with different compaction energies, these molds were submerged and finally failed with the California Bearing Ratio (C.B.R.) test; obtaining the following results: the control test yielded a unit weight of 20,804 kN / m3 at 95% of the CBR while the calamine test gave a value of 19,859 kN / m3.